2018
DOI: 10.1111/codi.14238
|View full text |Cite
|
Sign up to set email alerts
|

Is trans‐anal total mesorectal excision really safe and better than laparoscopic total mesorectal excision with a perineal approach first in patients with low rectal cancer? A learning curve with case‐matched study in 68 patients

Abstract: The TATME learning curve seems to be associated with a significant rate of intra-operative complications. Because no significant benefit has been reported to date, more evidence is needed before TATME can be considered as a better approach than laparoscopic TME with a perineal approach first in patients with low rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 31 publications
1
67
1
Order By: Relevance
“…One thousand two hundred and forty-seven citations were retrieved from the search strategy. Finally, twelve studies [24][25][26][27][28][29][30][31][32][33][34][35] were included in the analysis, with a total of 899 patients (411 patients in TaTME group, 488 patients in LaTME group) ( Figure 1). The characteristics of eligible studies are shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One thousand two hundred and forty-seven citations were retrieved from the search strategy. Finally, twelve studies [24][25][26][27][28][29][30][31][32][33][34][35] were included in the analysis, with a total of 899 patients (411 patients in TaTME group, 488 patients in LaTME group) ( Figure 1). The characteristics of eligible studies are shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…There were six studies [24-27, 31, 34] that reported CRM, eleven studies [24][25][26][28][29][30][31][32][33][34][35] that reported positive CRM, eight studies [24-27, 30, 32-34] that reported DRM and five studies [25,28,31,34,35] that reported positive DRM. No differences were found in these pathological outcomes ( Figure 5).…”
mentioning
confidence: 99%
“…Nevertheless, due to its complexity, the usage of different minimally invasive techniques in taTME is associated with a significant rate of intraoperative rectal, vaginal, or bladder injury during the learning curve, mainly due to the anatomical landmarks which are different from those during standard laTME from above. However, beyond the learning curve, the rate of intraoperative complications decreases [26,27,28]. Postoperative outcomes and oncological results of taTME and laTME were reported by several retrospective and comparative studies to be similar.…”
Section: Discussionmentioning
confidence: 99%
“…Although the learning curve of taTME has not been fully clarified 7,49) , the skills are believed to be difficult to acquire and care should be taken to avoid serious complications, especially in the early learning stages 50) . Deijen et al in their study performed pooled-analysis and compared clinical outcomes between low-volume (< 30 cases) and high-volume ("30 cases) centers.…”
Section: Education and Trainingmentioning
confidence: 99%